Integrasi Geopedologi dan Evaluasi Lahan untuk Mendiagnosis Kendala Tanah bagi Tanaman Jagung pada Lanskap Riparian Tropika - Bagus Adi Nugroho; Donny Dhonanto; Odit Ferry Kurniadinata; Penny Pujowati (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2026)
Maize (Zea mays L.) production in tropical riparian landscapes is strongly governed by spatial variability in soil–landscape interactions that control drainage conditions, rooting depth, and nutrient availability. This study aims to delineate geopedological landforms, evaluate maize suitability using a limiting-factor approach, and diagnose key landform-specific soil constraints. A GIS-supported geopedological framework with land suitability evaluation to spatially diagnose soil constraints affecting maize cultivation along the Kelinjau River, East Kalimantan, Indonesia. The study area was stratified into two geopedological landform units (permanently waterlogged peaty floodplains and undulating sandy terraces) using terrain analysis derived from digital elevation model (DEM) data, high-resolution satellite imagery, and field surveys. Climatic, soil physical and chemical, hydrological, and terrain characteristics were quantified using field observations, laboratory analyses, and geospatial datasets, and maize suitability was assessed using a land-characteristic–crop-requirement matching approach based on the principle of limiting factors. The results indicate that climatic and topographic conditions are spatially uniform and generally favorable for maize cultivation, whereas soil-related variables exert dominant control on suitability outcomes. Both landform units were classified as marginally suitable (S3). On peaty floodplains, low nutrient availability (particularly phosphorus) constitutes the primary limitation, while sandy terraces are constrained by impeded drainage, shallow effective soil depth, and nutrient deficiencies. These findings highlight the importance of landform-based spatial stratification in revealing process-driven soil limitations and demonstrate that integrating geopedology with spatial land evaluation enhances the diagnosis of constraints on maize suitability, thereby supporting targeted and sustainable land management in heterogeneous riparian landscapes.